2018
DOI: 10.1111/raq.12246
|View full text |Cite
|
Sign up to set email alerts
|

A literature review as an aid to identify strategies for mitigating ostreid herpesvirus 1 in Crassostrea gigas hatchery and nursery systems

Abstract: An understanding of husbandry strategies and any associated risk factors is important for designing management control measures that can reduce mortality in Pacific oysters, Crassostrea gigas, caused by ostreid herpesvirus 1 (OsHV-1). The type of culture facility can be considered in relation to the potential pathways that could lead to the entry of a pathogen and its survival. In addition, the animal host (e.g. age, physiological state, selective breeding programmes), husbandry procedures (e.g. stocking densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 123 publications
(250 reference statements)
0
15
0
Order By: Relevance
“…However, aquaculture hatchery supply of C. gigas spat is inconsistent due to larval mortality events (Robert and Gerard, 1999), which can be caused by OsHV-1 (Barbosa-Solomieu et al, 2005;Hine et al, 1992;Renault et al, 2000). Our results demonstrate that it is possible to utilize transgenerational immune priming to reduce mortalities in hatchery production of C. gigas, thus challenging the concept that such therapies cannot be adapted for oyster aquaculture (Pernet et al, 2016;Rodgers et al, 2018).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 80%
“…However, aquaculture hatchery supply of C. gigas spat is inconsistent due to larval mortality events (Robert and Gerard, 1999), which can be caused by OsHV-1 (Barbosa-Solomieu et al, 2005;Hine et al, 1992;Renault et al, 2000). Our results demonstrate that it is possible to utilize transgenerational immune priming to reduce mortalities in hatchery production of C. gigas, thus challenging the concept that such therapies cannot be adapted for oyster aquaculture (Pernet et al, 2016;Rodgers et al, 2018).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 80%
“…During mass mortality of the bay scallop larvae in the southern regions of Korea, it was observed that 5–10‐day‐old larva sank to the bottom of the tank. Based on this observation, this study focused on OsHV‐1, OVVD, V. coralliilyticus and V. tubiashii infections which were have been reported to demonstrate similar symptoms (Elston & Wilkinson, ; Farley et al, ; Rodgers, Arzul, Carrasco, & Furones Nozal, ; Sugumar, Nakai, Hirata, Matsubara, & Muroga, ; Tubiash, Chanley, & Leifson, ).…”
Section: Resultsmentioning
confidence: 98%
“…Since the rise of OsHV‐1‐associated mortalities in farmed C. gigas , integrated strategies have been used to mitigate the disease impacts, primarily through epidemiology, improved husbandry, selective breeding for disease resistance, and surveillance and biosecurity (Pernet et al, 2016; Rodgers et al, 2018). Current biosecurity measures are designed to prevent or control the spread of the disease, and policies are developed and revised based on the current state of knowledge.…”
Section: Figurementioning
confidence: 99%
“…Oyster farmers commonly move stocks between growing areas according to life stage to optimize husbandry and business management, environmental conditions and economics. These stock movements represent an extremely high risk for the translocation of diseases between infected and non‐infected areas (Brenner et al, 2014; Pernet et al, 2016; Rodgers et al, 2018). Breeding Pacific oysters also involves a number of stock movements, and where OsHV‐1 μvar is endemic, biosecurity measures are implemented (Castinel et al, 2015; Degremont & Benabdelmouna, 2014).…”
Section: Figurementioning
confidence: 99%